Sistem Pendukung Keputusan Menentukan Prioritas Tujuan Wisata Daerah pada Kabupaten Karo dengan Metode TOPSIS - Jimmi Herdianda Gurusinga; Bosker Sinaga; Anita Sindar RM Sinaga (Teknik Informatika Universitas Pamulang, 2020)
There are approximately 20 tourist objects in the Karo Regency area that are close to each other, such as Gundaling Hill, Lumbini Nature Park, Fun Land Mickey Holiday and other places. The main problem is designing a system using the SPK in determining the priority of regional tourist destinations in Karo Regency using the TOPSIS method. Problem solving steps are carried out from problem identification, determining alternative solutions to problems that arise so that the best decisions can be made. The weight of the criteria to determine the preferred criteria. The greater the weight, the more priority. Weights for each criteria for determining priority destination of tourist attractions, Distance from Berastagi (weight 30%), Facilities and Facilities (weight 15%), Access (15%), Type of Tourism (weight 20%), Entrance Fee (Weight 15%), Culinary (weight 5%), and internet network (5%). The preference value (V) produces alternatives that are ordered from largest to smallest. The biggest preference is tourism priority, in this case Kubu Berastagi Hill becomes a priority destination based on criteria.